Completely Closed Filter in BN -Algebra - Ramadhan, Andi Rio; Gemawati, Sri; Kartini, Kartini (Department of Mathematics, Faculty of Sciences and Technology, UIN Syarif Hidayatullah, 2025)
A BN-algebra (A; *,0) is a non-empty set A equipped with a binary operation * and a constant 0, which satisfies the following axioms: (B1) a*a=0, (B2) a*0=a, and (BN) (a*b)*c=(0*c)*(b*a) for all a,b,c ∈A. A subset I of A is called an ideal in A if it satisfies (i) 0∈I, (ii) if b∈I and a*b∈I imply a∈I, for all a,b∈A. This paper presents an original investigation on the completely closed filter in BN-algebra, a topic that has not been extensively explored in previous research. The concepts of filter, closed filter, and completely closed filter in BN-algebra are defined, which can always be associated with the concept of an ideal in BN-algebra. It begins by defining a filter in BN-algebra and then providing additional conditions to make it a closed and completely closed filter. The results show that every filter in BN-algebra has a condition (D), and every non-empty subset of BN1-algebra is a closed filter. Furthermore, every normal ideal in BN-algebra, ideal in Coxeter algebra, and subalgebra in BN1-algebra is a completely closed filter.Keywords: BN-algebra; Completely closed filter; Filter; Ideal. AbstrakBN-Aljabar (A; *,0) adalah himpunan tak kosong A yang dilengkapi dengan operasi biner * dan konstanta 0, yang memenuhi aksioma berikut: (B1) a*a=0,(B2) a*0=a, dan (BN) (a*b)*c=(0*c)*(b*a) untuk setiap a,b,c ∈A. Subhimpunan I dari A disebut ideal di A jika memenuhi: (i) 0∈I, (ii) untuk setiap b∈I dan a*b∈I mengakibatkan a∈I, untuk setiap a,b∈A. Dalam artikel ini, kami menyajikan sebuah studi baru tentang filter tertutup lengkap dalam BN-aljabar, sebuah topik yang belum banyak dieksplorasi dalam penelitian sebelumnya. Konsep filter, filter tertutup, dan filter tertutup lengkap dalam BN-Aljabar didefinisikan, yang mana selalu dapat dikaitkan dengan konsep ideal dalam BN-Aljabar. Dimulai dengan mendefinisikan filter dalam BN-aljabar, kemudian memberikan kondisi tambahan untuk menjadikannya filter tertutup dan filter tertutup lengkap. Hasil yang diperoleh adalah setiap filter dalam BN-Aljabar dengan kondisi (D) dan setiap subset tak kosong dari BN1-aljabar merupakan filter tertutup. Lebih jauh, setiap ideal normal dalam BN-aljabar, ideal dalam Coxeter aljabar, dan subaljabar dalam BN1-aljabar merupakan filter tertutup lengkap.Kata Kunci: BN-aljabar; Filter tertutup lengkap; Filter; Ideal. 2020MSC: 03G25, 03G10